Acupuncture for adult lung cancer of patient-reported outcomes: A systematic review and meta-analysis - Xi, Ziqi; Wei, Xuqiang; Ye, Zi; Wang, Ke; Zhou, Jia (Frontiers in Oncology, 2022)
Purpose: This systematic review and meta-analysis aims to assess the effects of acupuncture on patient-reported outcomes (PROs) in adults with lung cancer. Methods: Electronic databases including PubMed, Embase, Cochrane Library, Web of science, CNKI, CQVIP, Wanfang Data, SinoMed, and grey literatures was retrieved from inception to 1 July 2022 for randomized controlled trials (RCTs). Acupuncture was defined as an experimental intervention, and the patients of the control groups included either treatment including conventional therapy (usual care, sham/placebo acupuncture, pharmacotherapy including Western medicine and Chinese traditional medicine). PROs for this study were measured by 7 scales of primary outcomes including Karnofsky Performance Status (KPS), the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30), Functional Assessment of Cancer Therapy-Lung (FACT-L), Functional Assessment of Cancer Therapy Lung Cancer Subscale (FACT-LCS), Leicester Cough Questionnaire (LCQ score), the MOS item short from health survey (SF-36), and the St George’s respiratory questionnaire (SGRQ), and 12 scales of secondary outcomes. Cochrane Collaboration’s tool was used to assess the risks of bias. Data were combined and analyzed with RevMan 5.4 and Stata/SE 16.0. Results: We retrieved 3,002 lung cancer patients from 33 trials. KPS included with 1,000 patients showed that acupuncture could significantly improve quality of life (QOL) compared with control group regardless of different tumor-node-metastasis (TNM) stage or different stage of disease. The study showed that acupuncture significantly improved lung cancer-related symptoms in QOL, pain, nausea and vomiting, insomnia, anxiety and depression, fatigue and constipation compared with the control group. Eight RCTs reported the occurrence of adverse events, whereas 4 reported none and 4 RCTs reported the events in the observation group were significantly less than those in the control group. Conclusion: Acupuncture proved to be a promising intervention, both postoperatively and after chemotherapy, and should be recommended as a beneficial alternative strategy to promote PROs in lung cancer patients at all stages of application. We suggest more rigorous clinical trials of acupuncture for lung cancer in the future and more emphasis on the effect of acupuncture in patients with lung cancer on their PROs mainly in the aspect of QOL.